Payback of natural gas turbines: A retrospective analysis with implications for decarbonizing grids. (December 2021) - Carvalho, Rexon; Hittinger, Eric; Williams, Eric
Abstract: The low capital cost, low lead times, and flexible operation of natural gas combustion turbines are qualitatively different from other power generation technologies and have the potential for faster investment payback. We explore this hypothesis with a retrospective analysis of natural gas combustion turbine economics in six locations, with revenue from energy, frequency regulation, reserve, and capacity markets. Using historical data, we find payback periods from 8.5 to 15 years. Gas turbines can be financially justified with a single profitable decade of service and are thus more economically compatible with a decarbonizing grid than other types of fossil fuel infrastructure. Highlights: Gas turbines have the potential for faster investment payback than most generators. In a retrospective analysis, we find gas turbine payback periods of 9–17 years. Low natural gas prices and profitable ancillary services support turbine economics. Energy storage can compete with gas turbines in the future, though imperfectly.